Religious Minority and Peaceful Coexistence: The Dynamics of the Ahmadiyya Community in Malang, Indonesia - Widiyanto, Asfa; Setiawan, Mohamad Nur Kholis; Rohmat, Nur Fajriyah; Maesur, Sidqon (Universitas Islam Negeri Mataram, 2024)
The position of the Ahmadiyya is problematic since it claims to be a part of the Muslim community, but it is considered a deviant sect by the mainstream Sunni Muslims in Indonesia. There has been persecution and violence towards this minority. The violence towards the Ahmadiyya increased most notably after the issuance of a joint ministerial decree in 2008, which limits the activities and proselytization of the Ahmadiyya. Interestingly, although affected by the national and regional discourse on the Ahmadiyya, the Ahmadiyya community in Malang, East Java, still lives peacefully with other faith communities. By employing qualitative content analysis, the present study examines the dynamics of the Ahmadiyya as a religious minority in the context of a plural society in Malang, East Java. More specifically, it investigates two main research problems, namely the Ahmadiyya community’s agency in response to the limitation of their activities and the socio-political and socio-religious factors relatively supporting peaceful life of the Ahmadiyya community. This study reveals a distinct picture that stays in contrast to the majority of Ahmadiyya communities in Indonesia, which is often associated with discrimination and persecution.